A Linked Data Analysis Exploring the Real-World Burden and Hospital-Related Cost of Sarcoma in Western Australia: 1982 – 2016 - Wright, Cameron; Halkett, Georgia; Carey Smith, Richard; Moorin, Rachael (International Journal of Population Data Science, 2020)
Introduction Because sarcomas are a rare group of malignancies, centralised referral and management improves outcomes. To plan centralised care, an understanding of disease burden is essential. Epidemiological studies on sarcoma from Australia are lacking, as previous studies have focused on a sarcoma type (e.g. soft tissue) or anatomical sites. As notification of all cancer diagnoses is required in Western Australia (WA), routinely collected data provides a platform to improve understanding of the sarcoma burden and associated cost. Objectives and Approach This study aimed to determine incidence, prevalence, relative survival and cost of cancer-related hospitalisation for sarcoma in WA. Routinely linked cancer registry, hospital morbidity and death registration data from 1982 to 2016 were used. All new sarcoma cases among WA residents were included, using the Information Network on Rare Cancers (RARECARENet) definitions. To provide a reference point, comparisons were made with female breast, colorectal, prostate and lung cancers. Results The age-standardised incidence and prevalence of STS increased over time, while bone sarcoma remained more stable. For 2012-16, the combined sarcoma crude annual incidence was 7.3 per 100,000, with the majority of these soft tissue sarcoma (STS, incidence of 5.9 per 100,000). Five-year relative survival for the period 2012-16 for STS was 65% for STS, while five-year relative survival was 71% for bone sarcoma. This was higher than lung cancer, but lower than breast, colorectal and prostate cancer. Cancer-related hospitalisations cost an estimated (Australian) 29.1 million over the period. Conclusion / Implications The analysis of health service use showed sarcoma had a lower mean episode of cancer-related hospitalisation compared to the reference cancers in 2016, but the mean cost per prevalent person was higher for sarcoma than for female breast, colorectal and prostate cancer. STS incidence increased over time in WA, with an increasing proportion of people diagnosed aged ≥65 years.